Kontribusi Pusat Oleh-Oleh Khas Bali Terhadap Desa Batubulan - Kurniadi, I Made Pendhi; Pujani, Ni Luh Putu Kerti (JURNAL DESTINASI PARIWISATA; Vol 6 No 2 (2018): VOL 6, NO 2 (2018): (JULY - DECEMBER) JURNAL DESTINASI PARIWISATA, 2019)
This research aims to know the economic contributions in Batubulan village of Center by Bali. This research was conducted at the Balinese Souvenirs Centre and at Batubulan village environment, Sukawati District, Gianyar Regency. The scope in this research is the economic contributions such as labour absorption, development of other economic structure due to the Balinese Souvenirs Center, village incomeData collection techniques used included observation, structured interview, and documentary method. The technique of determination of informants used is purposive sampling. Descriptive qualitative used to analyze the data. In this study, the first thing is data collection. After getting all data, the next step is to conduct discussions and make conclusions. The overall attempt to capture the realities in the field in according with the research and we strive to earn the meaning so that it can be known to the social impact of economic center by Bali against local communities Batubulan village and its absorption of labor from local communities Batubulan village. The presence of the Bali souvenirs center in Batubulan village gives contributions for people in Batubulan village. In terms of the absorption of local product is still low because the craft of stone and sculpture cannot be marketed in Bali Souvenirs Centre. The existence of the Bali souvenirs center also gave rise to local hawkers who made this profession as a sideline. Besides the opening of employment at Bali souvenirs center also came Bali citizens also features from outside Bali so gave effort to boarding houses a business opportunity for the villagers. Bali souvenirs center also gave contribution to Batubulan village, traditional village, Banjar, and youth organizations in it. Keywords: Local Villagers, Contribution, Economy